Improving learning cultures in further education - James, David 1956-; Biesta, Gert; Colley, Helen (Improving learning TLRP., 2007)
Based upon findings of the 'Transforming Learning Cultures in Further Education' research project, this book argues that there is scope for improvement in further education. It develops a way of understanding educational improvement that focuses on the formation and transformation of the practices through which students learn.